The Effect of Return On Assets (ROA) on The Expenditure of Zakat Funds in Islamic Banks in Indonesia - Munir, Muhammad (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
This study aims to determine the effect of return on assets on the expenditure of zakat funds in Islamic banks in Indonesia. To find out the results of the research, the researchers used a quantitative approach with this type of research using quantitative descriptive methods. Quantitative descriptive research is a research that provides an overview of the effect of return on assets on the expenditure of zakat funds in Islamic banks in Indonesia. The results of his research indicate that Return on Assets has a significant effect on the expenditure of zakat funds. The ROA variable has a significant effect on the expenditure of zakat funds in Islamic banks. This result is in accordance with the probability value which shows (0.05 > 0.0000). This means that the greater the ROA value obtained, the greater the expenditure of zakat funds on Islamic banks, because the potential for a greater ROA will have an impact on increasing zakat funds.